The Rhetoric of the five speeches of Senator Miriam Defensor-Santiago - Gulanes, Giovanni L.
This study was conducted in view of the of the significance of rhetoric not only in understanding the personal, political, and professional prudence of Senator Mirriam Defensor-Santiago, but also in appreciating its role in the pursuit of our nation towards a free and democratic society. The study aimed to analyze and determine what kind of rhetoric Senator Santiago had in five selected privilege speeches she delivered during the formal sessions of the Senate. To systematize this, Kenneth Burke's Dramatistic Pentad with its five elements ? act, scene, agency, agent and purpose ? was needed. And in the discussion of agency, the study was further analyzed by using Aristotelian principle to determine and quantify in every paragraph of every speech the persuasive modes used: ethos, logos, and/or pathos.In addition, the study also analyzed what rhetorical devices or any style that were identified with the speaker in the selected speeches. After the five elements of the pentad were identified in every speech and were examine how each element affected each other as reflected in their ratios, it was found out that agent or the speaker herself was the predominant source of motive of the communicative act. It was the central element that influenced other elements of the pentad immaterial of the issues and scenes of the different speeches. Also, it was concluded that Senator Santiago, the agent, made use more of logical appeal (logos) compared to emotional appeal (pathos). This was reflected in her fondness of using legal provisions and analytical reasoning to substantiate her arguments. However, there could be no objective comparison to the ethos or the credibility of the agent, because it could not be just be an effect of the text of the speech, but an overwhelming product of her general background as a person, as politician, and as professional. It was conclusive that the kind of rhetoric Senator Santiago had in the selected speeches was brought about by the agent's ethical position as a distinguished senator, a staunch oppositionist, an exceptional intellectual, an anti-corruption crusader, a legal expert, and a defeated presidential candidate. Limited studies in the Philippines setting have been found in this area: hence, the results of this study would provide additional information on rhetorical criticism of prominent political personality using the ?dramatistic pentad? of Kenneth Burke and ?persuasive modes? of Aristotle.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication